2023
DOI: 10.1111/cns.14200
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviated depression‐like behaviors in ventromedial prefrontal cortex of chronic unpredictable mild stress‐induced rats: Increasing synaptic transmission and phosphorylating dopamine transporter

Abstract: Aims Electroacupuncture (EA) shows advantages in both clinical practice and depression animal models. Dopaminergic‐related dysfunction in the prefrontal cortex (PFC) may be a hidden antidepressant mechanism of EA, where dopamine transporter (DAT) plays an essential role. This study aimed to investigate the synaptic transmission and DAT‐related changes of EA in depression. Methods Male Sprague–Dawley rats were subjected to 3‐week chronic unpredictable mild stress (CUMS). The successfully modeled rats were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Electroacupuncture (EA) may exert its antidepressant effects by regulating dopaminergic correlates in the PFC, with DAT playing a key role. 53 Behavioral tests 54 found that electroacupuncture treatment was able to alleviate depression-like behaviors triggered by chronic unpredictable mild stress (CUMS). EA improves neural function by enhancing synaptic transmission in the ventromedial prefrontal cortex (vmPFC) and upregulating spontaneous excitatory postsynaptic current amplitudes.…”
Section: Acupuncturementioning
confidence: 99%
“…Electroacupuncture (EA) may exert its antidepressant effects by regulating dopaminergic correlates in the PFC, with DAT playing a key role. 53 Behavioral tests 54 found that electroacupuncture treatment was able to alleviate depression-like behaviors triggered by chronic unpredictable mild stress (CUMS). EA improves neural function by enhancing synaptic transmission in the ventromedial prefrontal cortex (vmPFC) and upregulating spontaneous excitatory postsynaptic current amplitudes.…”
Section: Acupuncturementioning
confidence: 99%